2001
DOI: 10.1038/sj.jhh.1001218
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dietary and non-dietary factors of hypertension and normal blood pressure in a Chinese population

Abstract: The aim of this study was to compare the differences of dietary and non-dietary factors in hypertension and normal blood pressure (BP) of Chinese urban people. Two cross-sectional population surveys were carried out in Tianjin, one of the three largest cities in China. A total of 2068 subjects aged 35-64 years were selected by a random stratified cluster sampling, 367 men and 395 women were hypertensive, and 623 men and 683 women had normal BP. The diet was assessed by food weighing plus consecutive individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…The obesity-related insulin-resistance syndrome, which describes a cluster of metabolic abnormalities (insulin resistance, hypertension, dyslipidaemia and impaired glucose regulation), has been recognised to play an important role in the development of type 2 diabetes [36][37][38][39][40]. A high intake of dietary sodium and the high urinary sodium to potassium ratio have been shown to have a direct relationship with essential hypertension [10][11][12][13][14][15]. Adjusted for age, sex, study year, education, physical activity (low, moderate and high), smoking status (never, past and current smoking of 1-19 or ≥20 cigarettes/day), alcohol consumption (0, 1-100 and >100 g/week), coffee consumption (0-2, 3-6 and ≥7 cups/day), frequency of vegetable consumption (<1 time/week, 1-2 times/week, 3-5 times/week, 6-7 times/week), frequency of fruit consumption (<1 time/ week, 1-2 times/week, 3-5 times/week, 6-7 times/week), frequency of sausage consumption (<1 time/month, 1-2 times/month, 1 time/ week, 2 times/week, almost daily, >1 time/day), bread consumption (slices/day) and saturated fat consumption (g/day) c Adjusted for variables in model 2 and systolic blood pressure and antihypertensive drug treatment at baseline and during follow-up d…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obesity-related insulin-resistance syndrome, which describes a cluster of metabolic abnormalities (insulin resistance, hypertension, dyslipidaemia and impaired glucose regulation), has been recognised to play an important role in the development of type 2 diabetes [36][37][38][39][40]. A high intake of dietary sodium and the high urinary sodium to potassium ratio have been shown to have a direct relationship with essential hypertension [10][11][12][13][14][15]. Adjusted for age, sex, study year, education, physical activity (low, moderate and high), smoking status (never, past and current smoking of 1-19 or ≥20 cigarettes/day), alcohol consumption (0, 1-100 and >100 g/week), coffee consumption (0-2, 3-6 and ≥7 cups/day), frequency of vegetable consumption (<1 time/week, 1-2 times/week, 3-5 times/week, 6-7 times/week), frequency of fruit consumption (<1 time/ week, 1-2 times/week, 3-5 times/week, 6-7 times/week), frequency of sausage consumption (<1 time/month, 1-2 times/month, 1 time/ week, 2 times/week, almost daily, >1 time/day), bread consumption (slices/day) and saturated fat consumption (g/day) c Adjusted for variables in model 2 and systolic blood pressure and antihypertensive drug treatment at baseline and during follow-up d…”
Section: Discussionmentioning
confidence: 99%
“…Low intake of potassium and a high urinary sodium to potassium ratio have indicated a direct relationship with essential hypertension [10][11][12][13][14][15]. A significant inverse relationship between magnesium intake and the risk of diabetes has been found in several prospective studies [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A large body of research has demonstrated that being overweight or obese (as assessed by the BMI) is associated with elevated blood pressure (BP) levels and increased risk for hypertension. 5 For example, in a random stratified cluster sample of 2068 Chinese men and women hypertensive patients of both genders had significantly higher mean BMI than their normotensive counterparts. 5 Nevertheless, controversy has arisen with regard to the appropriateness of a universal BMI definition of obesity.…”
mentioning
confidence: 98%
“…5 For example, in a random stratified cluster sample of 2068 Chinese men and women hypertensive patients of both genders had significantly higher mean BMI than their normotensive counterparts. 5 Nevertheless, controversy has arisen with regard to the appropriateness of a universal BMI definition of obesity. Based on the WHO criteria using BMI estimates, o5% of the Chinese population is obese 6 and it has been suggested that this is a gross underestimation of the prevalence of obesity and consequently those at risk for CVD.…”
mentioning
confidence: 98%